2018
DOI: 10.1016/j.prevetmed.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of contact network structure and the impact on foot-and-mouth disease transmission

Abstract: The movements of livestock between premises and markets can be characterised as a dynamic network where the structure of the network itself can critically impact the transmission dynamics of many infectious diseases. As evidenced by the 2001 foot-and-mouth disease (FMD) epidemic in the UK, this can involve transmission over large geographical distances and can result in major economic loss. One consequence of the FMD epidemic was the introduction of mandatory livestock movement restrictions: a 13-day standstil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…The spatial distribution will also be different from June. While the Census data are the best denominator for the pig sector (5,11) and cattle movement data are now used to provide the numbers of cattle for the June Census, for sheep the SGI is more usually used (13,30). In this study, the gross analysis of within-country non-slaughter movements demonstrated this spatially dynamic nature of the Scottish sheep population and provided context for discussion with regard to the fifth challenge (direct move only).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution will also be different from June. While the Census data are the best denominator for the pig sector (5,11) and cattle movement data are now used to provide the numbers of cattle for the June Census, for sheep the SGI is more usually used (13,30). In this study, the gross analysis of within-country non-slaughter movements demonstrated this spatially dynamic nature of the Scottish sheep population and provided context for discussion with regard to the fifth challenge (direct move only).…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, published literature of analyses of animal movement data has focused on network analysis and risk-based surveillance, predominantly in the cattle and pig sectors [e.g., (6)(7)(8)(9)(10)(11)]. Sheep sector movements have been included where they contribute to the spread of specified disease(s) under investigation (12,13) or where a larger scale, multi-sector, perspective is taken (14). There are a few publications of sheep population demographics (15,16) and network analyses (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, during this period, we observed an increase in the number of nodes and 386 connections; therefore, a given node would require more steps to reach another farm, within the 387 network which could alone reduce the speed of disease transmission (Vidondo and Voelkl, 388 2018 However, these followed the assumption that movement aggregation would not overestimate or 397 introduce edge biases (Vidondo and Voelkl, 2018). It has been suggested that to some extent, 398 static networks provide useful information about disease related risks (Mohr et al, 2018). pig transport data demonstrated that only a small fraction of 0.34% of the farms was connected 421 within one month (Sterchi et al, 2019).…”
Section: ‫ݐ‬mentioning
confidence: 95%
“…Thulke et al 20 also found that movement restrictions were more impactful in their model than pre-emptive culling in limiting the spread of classical swine fever in pigs. Mohr et al 21 recently looked at the impact of altering the contact network structure of livestock in Scotland on simulated foot-and-mouth disease dynamics. Optimal control measures have been studied extensively for plant diseases as well, even more so than for animal diseases.…”
Section: Related Workmentioning
confidence: 99%